DESAIN DAN IMPLEMENTASI WEB SMP ISLAM NGEBRUK MENGGUNAKAN PHP DAN MYSQL - Muchammad Ismail Hamzah (Universitas Bumigora, 2017)
In accordance with the technological advances of web-based information delivery via the internet has more value, because the information can be delivered easily, quickly, spacious and interactive. Because this way, information is simply inserted into the web and within seconds the information can be accessed globally.Submission of this information has not been used in Ngebruk Islamic Junior High School, Sumberpucung District, Malang Regency. Submission of the information in these schools still use manual way, such as by mail, bulletin boards, or orally. Surely this way less effective and efficient, since it requires a lot of expenses such as the purchase of paper, printing machine and maintenance, ink, and its scope was limited to the scope of the school.To reduce the above problems, the delivery of information in this school need to use web media created with the PHP programming language and MySQL. PHP is a programming language that is used to allow users to process information on the web, while MySQL is the software used to store the information on the web. Once the web is run online, the school entered information to the web, can be accessed via intenet by anyone without the limited space and time.